Sliding mode based fault detection, reconstruction and fault tolerant control scheme for motor systems. (July 2015) - Mekki, Hemza; Benzineb, Omar; Boukhetala, Djamel; Tadjine, Mohamed; Benbouzid, Mohamed
Abstract: The fault-tolerant control problem belongs to the domain of complex control systems in which inter-control-disciplinary information and expertise are required. This paper proposes an improved faults detection, reconstruction and fault-tolerant control (FTC) scheme for motor systems (MS) with typical faults. For this purpose, a sliding mode controller (SMC) with an integral sliding surface is adopted. This controller can make the output of system to track the desired position reference signal in finite-time and obtain a better dynamic response and anti-disturbance performance. But this controller cannot deal directly with total system failures. However an appropriate combination of the adopted SMC and sliding mode observer (SMO), later it is designed to on-line detect and reconstruct the faults and also to give a sensorless control strategy which can achieve tolerance to a wide class of total additive failures. The closed-loop stability is proved, using the Lyapunov stability theory. Simulation results in healthy and faulty conditions confirm the reliability of the suggested framework. Highlights: New sliding mode controller with an integral switching surface is designed. A nonlinear observer (SMO) is developed to detect and reconstruct actuator faults. A novel sensor-less fault tolerance based robust controller and observer is investigated. The proposed scheme can achieve tolerance to a wide class of total additive failures. Induction motor systems case study improves the efficiency of the proposed approach.